2014
DOI: 10.1093/nar/gku995
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal phosphorylation of HP1α increases its nucleosome-binding specificity

Abstract: Heterochromatin protein 1 (HP1) is an evolutionarily conserved chromosomal protein that binds to lysine 9-methylated histone H3 (H3K9me), a hallmark of heterochromatin. Although HP1 phosphorylation has been described in several organisms, the biological implications of this modification remain largely elusive. Here we show that HP1's phosphorylation has a critical effect on its nucleosome binding properties. By in vitro phosphorylation assays and conventional chromatography, we demonstrated that casein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 47 publications
7
79
0
Order By: Relevance
“…Phosphorylation of Pdd1p in Tetrahymena might also regulate its interaction with other proteins that are required for subsequent heterochromatin body formation. Alternatively, because phosphorylation and/or RNA binding of HP1 modulate its affinity to chromatin in some eukaryotes (13)(14)(15)37), Pdd1p phosphorylation may also modulate the physical dynamics of Pdd1p, which may be required for other heterochromatin proteins to be properly arranged on chromatin for heterochromatin body formation. Several proteins are known to be required for the formation of heterochromatin bodies in Tetrahymena (26,27,32), and the phosphorylation of Pdd1p may be essential for the chromatin localization of such proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of Pdd1p in Tetrahymena might also regulate its interaction with other proteins that are required for subsequent heterochromatin body formation. Alternatively, because phosphorylation and/or RNA binding of HP1 modulate its affinity to chromatin in some eukaryotes (13)(14)(15)37), Pdd1p phosphorylation may also modulate the physical dynamics of Pdd1p, which may be required for other heterochromatin proteins to be properly arranged on chromatin for heterochromatin body formation. Several proteins are known to be required for the formation of heterochromatin bodies in Tetrahymena (26,27,32), and the phosphorylation of Pdd1p may be essential for the chromatin localization of such proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, phosphorylation of the HP1 homolog Swi6 is required for transcriptional gene silencing by recruiting a histone deacetylase complex (12). In mammals, phosphorylation of serine (Ser) clusters at the N-terminal region of HP1α increases its affinity to H3K9me, presumably by inhibiting the DNA binding property of this protein (13,14). Consistently, in flies, substitutions of phosphorylated Ser residues of HP1a with alanine compromise heterochromatic gene silencing (15,16).…”
mentioning
confidence: 97%
“…Each of the HP1 proteins contain three domains, a chromodomain with high affinity for methylated H3K9, a hinge domain which may direct protein localization, as well as a C-terminal chromoshadow domain which allows for dimerization (Lachner et al 2001;Lomberk et al 2006;Nishibuchi et al 2014). While HP1 proteins generally associate with H3K9me2/3, phosphorylation of H3S10 by the Aurora B kinase causes dissociation of HP1β/γ but not HP1α from binding the chromatin fraction during cellular divisions (Nishibuchi et al 2014). Post-translational modifications of HP1 itself also influence its Studies using ChIP and quantitative real-time PCR have found enrichment of H3K9me3 in the coding regions of escape genes along the Xi.…”
Section: : Heterochromatin Protein 1 (Hp1)mentioning
confidence: 99%
“…Transcritional silencing, heterochromatin SUV39H1/2 [143] , G9a [248] , SETDB1 [249] JMJD1A/KDM3A [250] , JMJD1B/KDM3B [251] , JMJD1C/TRIP8, JMJD2A/KDM4A (B/C/D) [252] HP1 [253] , EED 17406994), TDRD7 [254] , MPP8 [255] , UHRF1/2 [256] , GLP [248] , CDY FAMILY [257] H3K27 me1/me2/me3, heterochromatin and facultative heterochromatin Transcritional silencing, heterochromatin, poised genes EZH2, EZH1 [258] JMJD1A/KDM3A, JMJD1B/KDM3B, KDM6A/UTX, JMJD3/KDM68, JMJD3/KDM6B [259] Cbx proteins [165] , EED [260] [ 166,261] H3K36 Ac Transcription activation GCN5, PCAF [244] [262]…”
Section: H3k27me3 or H3k9me3mentioning
confidence: 99%